Development of Illustration Stories as Media for Stimulating Student's Reading Interest - Rizkita Ayu Mutiarani; Ni Made Sri Hari Mahayoni (Sean Institute, 2023)
Technology for learning is also expanding rapidly. Technology in education aids students and teachers. Technology without direct engagement and transition time will make children lose interest, focus, and listen. To maintain student interest in reading. This research seeks to create learning media in the form of illustrated stories that will help students focus and be more engaged. The project aims to boost students' attention to interest, help teachers communicate with students, improve student learning, and expand schools' learning techniques. The research produced learning media in the form of illustrated stories with simple and cheerful concepts to fit the segmentation of the object of research, grade 3 elementary school students, so that students can easily understand the story and identify objects in the stories. The stories can also be used to teach students how to read.